ANALISIS PENGARUH BI RATE, JUMLAH UANG BEREDAR (M2) DAN KURS TERHADAP INVESTASI LANGSUNG DI INDONESIA TAHUN 2000-2019 - Arta Pande; Syapsan Syapsan; Isbah Ufira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze influence of the BI Rate, the Money Supply (M2) and Exchange Rate have on Direct Investment in Indonesia. This study uses independent variables consisting of the BI Rate, Money Supply (M2) and Exchange Rates, with the dependent variable being direct investment. The data used in this study are annual data from 2000-2019. The analytical method used is descriptive quantitative and analyzed in the long and short term with an error correction model (ecm) which is processed using E-Views version 11. The test results show that the short-term Money Supply (M2) has a significant positive effect on Direct Investment in Indonesia. Meanwhile, the exchange rate in the long term and short term has a significant positive effect on direct investment in Indonesia. In addition, the value obtained from adjusted R ^ 2 is 90.95% in the long term and 74.72% in the short term.Keywords:BI Rate, Money Supply, Exchange Rate and Direct Investment